Adaptive Fuzzy Control Approach for Dynamic Pantograph-Catenary Interaction - Karakose, Ebru; Gencoglu, Muhsin Tunay (Czech Technical Univ Prague, 2012)
In the World, especially in Europe high speed rail systems are increasingly becoming popular. Because of the environmental benefits, comfort, speed, time advantage and reliability of the electrical rail systems, their importance is more increasing. The interaction between the pantograph and the catenary is the most important factor affecting the quality of energy transmission. This article proposes a novel model design for pantograph-catenary system. The model was created using adaptive fuzzy logic controller. The aim of this article is to improve an effective and active control method for contact force between pantograph and catenary and to develop a pantograph-catenary system model without using conventional control methods. In addition, this study was given a detailed pantograph-catenary system model for the electrical train systems. The model was designed by using the Matlab-Simulink program and simulation results were obtained.
15th International Conference on Mechatronics (Mechatronika) -- DEC 05-07, 2012 -- Prague, CZECH REPUBLIC
Keywords: pantograph; catenary; active suspension systems; adaptive fuzzy logic controller